Alveolar Bone Loss at Maxillary and Mandibular Permanent First Molars in Periodontitis Patients: An Observational Study - Harish Kumar Shah; Rajesh shah; Sujaya Gupta; Harendra Mohan Singh; Md. Asdaq Hussain; Mohammed Shakeel Ahmad; Abanish Singh (Journal of Nepal Medical Association)
Introduction: Periodontitis is an inflammatory condition of periodontium that results in alveolar bone loss. Panoramic radiograph is one of the methods used to evaluate alveolar bone loss. However, in Nepal data quantifying the extent and site-specific pattern of alveolar bone loss using panoramic radiograph are still lacking. The objective of this study was to determine the amount of alveolar bone loss at the mesial and distal sites of maxillary and mandibular permanent first molars.